1984
DOI: 10.1111/j.1600-051x.1984.tb02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and periodontitis: Clinical effect of calcium medication

Abstract: In contrast to the generally held concept that periodontal disease is caused by microorganisms, Henriksson (1968) suggested that a nutritional deficiency of calcium might be the cause. He elicited secondary hyperparathyroidism in beagles from a low calcium/high phosphorus diet and found that the osteolytic demineralization of bone that followed seemed to involve alveolar bone more than other bones. In a report on 10 persons with advanced periodontal disease, Krook et al. (1972) stated that the disease was reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…In our study, calcium deficiency was not selected as a significant factor for periodontal disease. Likewise, another study also reported that calcium deficiency is not a main cause of periodontal disease, as they did not find any changes in marginal bone level or density in radiographic assessment (Uhrbom and Jacobson, 1984). Further studies are needed to determine the possible micronutrients that contribute to gingival or periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, calcium deficiency was not selected as a significant factor for periodontal disease. Likewise, another study also reported that calcium deficiency is not a main cause of periodontal disease, as they did not find any changes in marginal bone level or density in radiographic assessment (Uhrbom and Jacobson, 1984). Further studies are needed to determine the possible micronutrients that contribute to gingival or periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the intake of grapefruit leads to an increase in plasma vitamin C levels and improved sulcus bleeding scores. Uhrbom & Jacobson (1984) reported a placebo controlled trial investigating the effect of calcium supplementation (1 g per day for 180 days) on the periodontal condition of periodontitis patients but were unable to show an effect. The use of calcium and vitamin D oral supplements was evaluated retrospectively by Miley et al (2009) in subjects receiving periodontal maintenance therapy.…”
Section: Evidence From Nutritional Benefit Intervention Studiesmentioning
confidence: 99%
“…In other studies, low calcium intakes were associated with alveolar bone loss in periodontal disease patients and calcium supplementation decreased inflammation and crestal alveolar bone loss, and reduced probing depth and tooth mobility 24‐27 . However, other investigators were not able to reproduce these results 28 . More recently, analyses of the Third National Health and Nutrition Examination Survey (NHANES III), which included 12,000 adults, revealed significant associations between periodontal health and vitamin D and calcium intakes 29,30 .…”
mentioning
confidence: 98%